2009
DOI: 10.1128/jcm.01497-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of a Commercially Available Automated System for Extraction of Viral DNA from Whole Blood: Application to Monitoring of Epstein-Barr Virus and Cytomegalovirus Load

Abstract: The NucliSENS easyMAG automated system was compared to the column-based Qiagen method for EpsteinBarr virus (EBV) or cytomegalovirus (CMV) DNA extraction from whole blood before viral load determination using the corresponding R-gene amplification kits. Both extraction techniques exhibited a total agreement of 81.3% for EBV and 87.2% for CMV.Epstein-Barr virus (EBV) and cytomegalovirus (CMV) infections represent a significant clinical threat for immunocompromised patients. The frequent determination of EBV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…samples were randomly allocated to undergo manual or automated extraction, and the analyses were performed on the same days by the same operator who routinely used both methods. Our results are supported by earlier reports which showed that manual extraction methods were comparable [9][10][11] or less sensitive [12][13][14][15] than automated methods for other types of samples and micro-organisms. Besides, automated methods are associated with additional benefits, e.g.…”
Section: Discussionsupporting
confidence: 95%
“…samples were randomly allocated to undergo manual or automated extraction, and the analyses were performed on the same days by the same operator who routinely used both methods. Our results are supported by earlier reports which showed that manual extraction methods were comparable [9][10][11] or less sensitive [12][13][14][15] than automated methods for other types of samples and micro-organisms. Besides, automated methods are associated with additional benefits, e.g.…”
Section: Discussionsupporting
confidence: 95%
“…Routine virological studies included the detection of IgM and IgG antibodies to CMV (Siemens, Saint Denis, France) and the measure of CMV DNA load in whole blood using the CMV Rgene kit (Argene, Verniolle, France ) as previously described ( 25 ).…”
Section: General Procedures At Inclusionmentioning
confidence: 99%
“…Although various extraction systems have been used, 6 -8 comparisons between automated and manual systems are limited in number. 9,10 The QIAamp spin column method (Qiagen, Valencia, CA) is a widely used manual extraction system based on the adsorption of DNA to a silica gel membrane. With the processing of large batches of specimens, this system becomes extremely labor-intensive, however, and the high number of manual micropipetting steps increases the risk for repetitive motion injury and the potential for technical error.…”
mentioning
confidence: 99%